Collaborative stress of concrete-filled steel tube tied-arch beam-column support based on the double-layer elastic foundation beam theory - Jiazhu Tong; Hang Wang; Dalian Xu; Changjin Tian (Frontiers in Built Environment)
The construction of concrete-filled steel tube tied-arch bridges typically employs the “beam first and arch later” methodology. In this approach, tie beams are initially constructed on temporary supports, followed by the erection of the arch ribs. When post-construction loads—such as those from arch-rib supports and concrete-filled steel tubes—are applied, a synergistic force phenomenon occurs between the tie beam and temporary supports, which collectively bear these loads. To investigate the collaborative-force mechanism of the tie beam during construction, we developed a collaborative-force model based on Winkler’s double-layer elastic foundation beam theory. We derived equations for displacement, rotation angle, bending moment, and shear force of the tie beam under concentrated loads. Using a 72-m concrete-filled steel tube arch bridge as our research subject, we conducted a comparative analysis utilizing finite element methods. The results indicated that our derived formulas were consistent with those obtained through finite element meta-computing techniques. Under concentrated loading conditions, it was observed that the load increment at the location of the steel pipe column in the Bailey beam was significantly larger than what traditional averaging methods would predict. Conversely, load increments at both mid-span and pier locations of the Bailey beam were relatively small. Furthermore, it was found that variations in concrete strength grade had minimal impact on displacement, bending moment, and bearing ratio for both tie beams and Bailey beams. However, factors such as cross-sectional height of the tie beam and arrangement of sandwich buckle frames exerted considerable influence on both displacement and load-bearing ratios for these structural elements. Additionally, while arrangements within Bailey beams significantly affected displacements in both types of beams (tie beam and Bailey beam), their impact on bending moments and bearing ratios was comparatively less pronounced.